2004
DOI: 10.1128/jb.186.14.4568-4574.2004
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of the Heat-Stable ToxinastAGene into a Gifsy-2-Related Prophage ofSalmonella entericaSerovar Abortusovis

Abstract: The horizontal transfer and acquisition of virulence genes via mobile genetic elements have been a major driving force in the evolution of Salmonella pathogenicity. Serovars of Salmonella enterica carry variable assortments of phage-encoded virulence genes, suggesting that temperate phages play a pivotal role in this process. Epidemic isolates of S. enterica serovar Typhimurium are consistently lysogenic for two lambdoid phages, Gifsy-1 and Gifsy-2, carrying known virulence genes. Other serovars of S. enterica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Yet, there is no evidence of EAST1-dependent fluid secretion in animal studies or of an association of EAST1 with epidemic strains of E. coli with high diarrheagenic potential [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there is no evidence of EAST1-dependent fluid secretion in animal studies or of an association of EAST1 with epidemic strains of E. coli with high diarrheagenic potential [2].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Bacciu et al [2] indicated that an intergeneric transfer of virulence genes (involving the astA gene) via an insertion sequence (IS1414, encoding a transposase (tnpA) and astA in Salmonella) from E. coli together with studies reporting the presence of astA in bacterial genera besides E. coli, like Salmonella Agona [32] and Klebsiella pneumoniae [29] clearly indicate that horizontal transfer of virulence factors, including the astA gene, between bacterial genera occurs in nature and can account for the considerable distribution of the EAST1 gene in E. coli besides EAEC. Yet, there is no evidence of EAST1-dependent fluid secretion in animal studies or of an association of EAST1 with epidemic strains of E. coli with high diarrheagenic potential [2].…”
Section: Discussionmentioning
confidence: 99%
“…More significant are the four plaque-forming prophage, Gifsy-1, Gifsy-2, Fels-1, and Fels-2. These viruses are under selection because they include multiple genes and operons that increase the ability of Salmonella to infect and reside in mammalian hosts (Bacciu et al 2004;Coombes et al 2005;Figueroa-Bossi and Bossi 1999;Ho et al 2002). These elements are also potentially lethal if and when spontaneous induction leads to viral replication and cell lysis.…”
Section: Why Do Bacteria Evolve Significantly Different Supercoil Setmentioning
confidence: 99%
“…Detection of Gifsy-1 and Gifsy-2 phages was performed as previously described [3]. S. Typhimurium strain ATCC 14028s was used as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple virulence factors are involved in the pathogenesis of Salmonella. These virulence genes act together in a complex virulence function, and have been found on horizontally acquired DNA regions, such as pathogenicity islands, plasmids, transposons, and bacteriophages [3,4].…”
Section: Introductionmentioning
confidence: 99%